Dimensions of corporate social responsibility: a time for new discourse. (1st December 2008) - Arevalo, Jorge A.
This paper reviews the historic approaches to corporate social responsibility and traces the concept back to the 1950s. It highlights the progress in interpretation, definition, and modelling dimensions from a historical perspective. We present the progress by decades and propose an alternate discourse(s) for the study of CSR based on our 50-year analysis of its gradual development. The paper also suggests that scholars consider borrowing of discourse from more research disciplines in order to generate creative and innovative empirical research and methodology. We therefore introduce the concept of restructuring organisations and look into the strategies of multinationals and call for a unification of the two disciplines. By so doing, the global manager benefits from the advances in the field of social issues and our field of social responsibility will gain new insights into the studies of organisations.